Mise En Place Efficiency in the Kitchen of 18th Restaurant, the Trans Luxury Hotel - Idham Sakti Wibawa; Ilham Fajri; Kelly Tanuhadi (Gastronomy Tourism Journal, 2023)
This study aims to examine the efficiency of mise en place in the kitchen of the 18th restaurant, located in The Trans Luxury Hotel. Mise en place is a systematic and organized preparation practice carried out before cooking, involving the collection, preparation, and arrangement of all ingredients, equipment, and tools required during the cooking process. Efficiency in mise en place is crucial in achieving optimal performance in a restaurant kitchen, including time savings, increased productivity, and reduced errors.The research methodology utilized direct observation and interviews with kitchen staff at the 18th Restaurant. Data collection encompassed preparation time, efficiency of arrangement, equipment usage, and adherence to established mise en place procedures. Data analysis involved comparing actual preparation time with predetermined target times. The findings indicate that the implementation of mise en place in the kitchen of the 18th Restaurant still has some inefficiencies. Several factors influencing mise en place efficiency include a lack of coordination among employees, unavailability of required ingredients or equipment, and a lack of understanding of established procedures. Recommendations to enhance mise en place efficiency in the kitchen of the 18th Restaurant include improving training and understanding among employees regarding mise en place procedures, ensuring the availability of adequate equipment, and enhancing coordination among the kitchen team. Additionally, the implementation of supervision and control systems is necessary to ensure compliance with established mise en place procedures. This study provides a better understanding of the importance of mise en place efficiency in a restaurant kitchen and offers practical recommendations to enhance mise en place performance in the 18th Restaurant of The Trans Luxury Hotel. The findings can serve as a guide for restaurant management in optimizing preparation and organization in the kitchen, thereby improving operational efficiency and the quality of service provided to hotel guests.